2015
DOI: 10.1108/jmlc-04-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Perception of tax evasion as a crime in Turkey

Abstract: Purpose – The aim of this study is to investigate Turkish taxpayers’ perception of the severity of tax evasion relative to other crimes and violations. Design/methodology/approach – A questionnaire survey was administrated to 475 Turkish self-employed respondents. One sample t-test and one-way analysis of variance methods were used for data analysis. Findings – The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
1
18
0
2
Order By: Relevance
“…Primarily, economists within the scope of both microeconomic individual economic behaviour and macroeconomic public finance have extensively studied the subject of tax evasion (Ritsatos, 2014). This is because, according to Benk et al (2015), tax evasion is one phenomenon that causes loss of revenue and reduces the effectiveness of the tax system.…”
Section: Corruption-tax Evasion Nexusmentioning
confidence: 99%
See 3 more Smart Citations
“…Primarily, economists within the scope of both microeconomic individual economic behaviour and macroeconomic public finance have extensively studied the subject of tax evasion (Ritsatos, 2014). This is because, according to Benk et al (2015), tax evasion is one phenomenon that causes loss of revenue and reduces the effectiveness of the tax system.…”
Section: Corruption-tax Evasion Nexusmentioning
confidence: 99%
“…From the above discussions, individuals perceive tax evasion as a crime albeit comparatively less heinous. In whichever way it is perceived, tax evasion leads to financial bleeding, which denies emerging economies of the much required tax revenues to achieve SDGs (Benk et al, 2015).…”
Section: Does Corruption Cause Tax Evasion?mentioning
confidence: 99%
See 2 more Smart Citations
“…Although legally tax evasion is illegal, people in some countries still consider this action, not a serious crime. Benk et al (2015) found that the average person in Turkey views tax evasion as not a serious crime. They assess less tax evasion than accounting fraud.…”
Section: Introductionmentioning
confidence: 99%